Detecting amplicons of loop-mediated isothermal amplification - Shirato, Kazuya (Microbiology and immunology, 2019)
Loop-mediated isothermal amplification (LAMP) assays are used to detect diverse pathogens. Initially, LAMP amplicons were detected using electrophoresis; later, real-time monitoring based on turbidity was developed to overcome the problem of contamination with environmental DNA. Recently, real-time monitoring of fluorescence signals using a quenching primer and probe has improved the reliability of amplification signals. Here, methods of detecting LAMP amplicons are reviewed.